Antioxidant activities of the standardized water extract from fruit of phyllanthus emblica linn - Charoenteeraboon J. (2014)
Phyllanthus emblica Linn. is widely used in Thai traditional medicine for treatment of various diseases. The fruit of P. emblica is known as a rich source of vitamin C, and also contains a mixture of phenolic compounds. In this study, the standardized water extract of P. emblica fruit was prepared according to Thai Herbal Pharmacopoeia. Total polyphenol contents of the extract were equivalent to 34.22±1.74 g gallic acid/100g extract. Antioxidant activities of the P. emblica extract were evaluated by several methods, including DPPH and ABTS•+ radical scavenging assays and FRAP assays. The results showed that the extract has an ability of scavenging radicals generated by both DPPH and ABTS•+. Similar to Trolox, the water extract of P. emblica fruit also had a ferric reducing property. Additionally, the extract effectively inhibited H2O2-induced free radical production in human myeloleukemic U937 cells as measured by 2,7-DCF-DA. The results imply that the fruits of P. emblica are potential sources of natural antioxidants, which have free radical scavenging activity and might be useful for hepato-, cyto-, and radio- protection, as well as reducing oxidative stress in many pathological conditions.